La motivación y el rendimiento laboral en la Cooperativa de Ahorro y Crédito Virgen del Cisne del Cantón La Mana, año 2021. - Araque Arroyo, Erika Alejandra (2022)
For any company or organization, work motivation comprises a fundamental tool, which aims to show interest and satisfy its human talent with incentives that positively influence their behavior, thus improving their work performance, which is why this research was focused on Analyzing the motivation and its impact on the work performance of the Virgen del Cisne Savings and Credit Cooperative of The Mana canton, year 2021, for the improvement of administrative activities. Being necessary for this the use of historical, analytical, deductive methods and the types of research: field, bibliographic, as well as the level of research: quantitative, descriptive and correlational, for the collection of information used the interview technique. and employee surveys. To obtain a higher level of security about the suitability of the instrument, the IBM SPSS 26 program was used where the results of the pilot survey applied to 7 collaborators were entered, the Cronbach's Alpha reliability analysis was used, which yielded an index of 0.781. Once the corresponding calculations were developed and the results of the contrasts were analyzed, it was detected that the dimensions Management leadership-Remuneration system (0.760), Organizational structure-Well-being and health (0.790), Organizational structure-Training and Development (0.586), Leadership of the management - Promotion of job growth (0.644) presented the most significant correlations, in the same way it was determined that the variables motivation and work performance are correlated in a moderate positive way quantified through the results of 0.565 with a level of significance of 0.03. Therefore, the alternative hypothesis is accepted: Motivation affects the work performance of the Virgen del Cisne Savings and Credit Cooperative of The Mana canton, and the null hypothesis is rejected.